Boosting Metacognition through STAD and NHT: A Study of Multiethnic Middle Schoolers in Ternate - Ermin Ermin; Najamudin Marsaoly; Paramitha Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Metacognitive skills are essential for 21st-century learners, enabling students to plan, monitor, and evaluate their thinking processes. However, these skills remain underdeveloped among junior high school students in Ternate, particularly in multiethnic classroom settings. This study investigates the effectiveness of cooperative learning models—STAD, NHT, and a combined STAD–NHT model—in enhancing students' metacognitive skills across different ethnic groups. This quasi-experimental study employed a pretest–posttest nonequivalent control group design involving 76 multiethnic Grade VII students from four public junior high schools in Ternate City. Students were grouped into four treatment conditions: STAD, NHT, combined STAD–NHT, and conventional learning. Data on metacognitive skills were collected through an essay-based test aligned with Corebima’s rubric, and analyzed using ANCOVA with LSD post hoc tests to examine the effects of learning models, ethnicity, and their interaction. The combined STAD–NHT model produced significantly greater improvements in students’ metacognitive skills compared to individual models and conventional learning. Ternate ethnic students showed higher metacognitive gains than their Makian and Tidore peers. A significant interaction between learning models and ethnicity was found, indicating that sociocultural factors influenced the effectiveness of cooperative learning. Findings suggest that combining STAD and NHT can support metacognitive development in multiethnic classrooms. However, cultural responsiveness in instructional design is critical. Further research is needed to explore how cultural norms shape collaborative learning and metacognitive growth.